MANAJEMEN PROGRAM UNGGULAN MA’HAD BAGI MAHASISWA KIP KULIAH DI IAIN KERINCI - Netra Hayanti; Muhd. Odha Meditamar (STKIP Pesisir Selatan, 2025)
This study aims to analyze the management of the Ma'had flagship program for students receiving the Indonesia Smart Card for College (KIP-K) at IAIN Kerinci, covering aspects of planning, organizing, implementation, and evaluation. The background of this study is the importance of managing dormitory-based coaching programs to support government affirmative policies while shaping student character and competence. The method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation of Ma'had managers, program supervisors, and KIP Kuliah recipient students. The results show that program planning is carried out systematically through work meetings and annual evaluations with three main focuses, namely Arabic, English, and Tahfidz Al-Qur'an. The organization is collaborative between administrators, supervisors, and students, while implementation is adaptive and disciplined through peer tutoring, discussions, and memorization assignments. Evaluations are conducted in layers, including daily, weekly, and semester assessments, although non-academic aspects such as discipline and attitude still require more objective assessment instruments. Overall, the Ma'had flagship program at IAIN Kerinci is effective in improving the academic, spiritual, and character competencies of KIP Kuliah students